Integrating Sauyunan Local Wisdom into Educational HR Management: A Strategy to Foster Organizational Citizenship Behavior in Primary Schools - Nika Sintesa; Patoni Patoni; Ela Laela (Al-Qalam Institute, 2026)
This article aims to develop a conceptual framework for educational human resource management innovation by integrating the local wisdom of sauyunan and teachers' Organizational Citizenship Behaviour (OCB) in the context of elementary schools. This study employed a qualitative approach through a conceptual analysis of the literature on educational management, local wisdom, school culture, and teacher organizational behaviour. The findings indicate that sauyunan functions as cultural capital, strengthening cooperation, mutual support, trust, and harmony within the school organization. Meanwhile, teachers' OCB serves as a behavioural mechanism that transforms cultural values into voluntary, proactive, and collaborative actions beyond formal job requirements. The integration of sauyunan and OCB produces a contextual, participatory, and sustainable model of educational human resource management innovation that is relevant to the socio-cultural characteristics of elementary schools. The study implies that school leaders and policymakers should design teacher development strategies that do not rely solely on administrative or technological reforms, but also strengthen cultural values and voluntary organizational behaviour as foundations for improving school quality and institutional sustainability over time.